STUDENT CENTERED LEARNING MODEL IN SEA TRANSPORTATION STUDY PROGRAM AT MERCHANT MARINE POLYTECHNIC OF WEST SUMATERA - Putra, Riki Wanda; Yatno, Langan Driansyah Dwi; Kurniawan, Muhammad; Andini, Nisye Frisca (Jurnal Ilmu Pendidikan Ahlussunnah, 2024)
In order to realize the objectives of Outcome Based Curriculum (OBC), the Student Centered Learning (SCL) model is the main key. This study is aimed to describe the SCL learning model in the Sea Transportation study program at Poltekpel Sumbar. This research is qualitative research using descriptive methods and library research. The subjects were all lecturers at Poltekpel Sumbar, especially lecturers in the Sea Transportation study program. Data collection techniques were carried out by observation, interviews, and literature studies. Data analysis techniques were carried out by: (1) recording field observations and recording the interview process, (2) collecting all data from observations and interviews, and (3) making conclusions from the results of observations and interviews, (4) looking for literature references related to research from the Internet. The results explain that there are several SCL learning models in the Sea Transportation study program at Poltekpel Sumbar, namely: Self-Directed Learning (SDL), Simulation Based Learning (SBL), Observation Based Learning (OBL), Practice Centered Learning (PCL), Module Based Learning (MBL), and Technology Based Learning (TBL). Research suggestions for lecturers are to be able to apply the SCL model in the learning process and for students to motivate themselves to implement the SCL model for learning activities.